Spatial and temporal sedimentation changes in the Three Gorges Reservoir of China. Issue 4 (December 2015) - Gao, Peng; Wang, Zhao‐yin; Siegel, Donald
Abstract: This study examined the temporal trend of sedimentation in China's Three Gorges Reservoir (TGR) from compiled sediment data at multiple temporal scales. Based on decade‐averaged annual sediment loads, a decreasing trend of sediment supply between 1950s and 2000s was found, with a lower‐than‐expected mean sedimentation rate. From 2003 to 2013, the annual sediment supply generally decreased, with the annual sediment deposition rate being about 50% less than that predicted with prior numerical models. The reduced annual sedimentation rate was attributed to (relatively) small dam building within the upstream watershed, conservation activities and sand/gravel mining. Morphological changes at two cross sections within the TGR between 2003 and 2013 indicated that sediment deposition caused only limited bed accretion along the main course of the TGR. In the tail area of the TGR, where sediment transport ceases first, the sedimentation occurring between 2004 and 2013 was insufficient to impede navigation. These results indicate that at least as a first approximation sedimentation in the TGR is well controlled, making it a subdued 'river dragon'.